PEMANFAATAN DIRECTION API ( APPLICATION PROGRAMMING INTERFACE ) PADA LAYANAN GOOGLE MAP UNTUK PENCARIAN RUMAH IBADAH DI KOTAMADYA YOGYAKARTA PADA HANDPHONE BERBASIS ANDROID - Gunawan Addiwinoto; Hero Wintolo; Dwi Nugraheny (Compiler, 2012)
Since the smartphone android as open technology was found, the Users can take some advantages from Google’s map service which is exist in the application to build the applications service. API direction can using HTTP to determine the location of the inter-view destination, mileage and road routes that can be passed either as a text string or as a latitude or longitude that can be implemented through a Google map.By using this direction google map service, API, can be used this service to create a searching application service to search the houses of worship. Besides used  for knowing generally the houses of worship that exist around the Yogyakarta city, the determination of the shortest path is needed because in this life people often travel from one place to another by considering the efficiency of time, mileage and expenses.Searching service of the houses of worship is existed in the application, it can be tested in various service providers through the internet and GPS signal strength which is optimal enough to obtain the shortest distance with the direction on the map and with a percentage accuracy of the average distance between Google on the map with the actual distance of 99%.